Quantitative Research Review: Awareness and Adoption of Digital Marketing Strategies amongst Small and Medium Enterprise in Lagos State, Nigeria - Doyinsola Aduloju Ayokanmi (Britain International for Academic Research (BIAR) Publisher, 2025)
This study was conducted by Nduneche Ezurike in the Department of Marketing, LIGS University, Honolulu, Hawaii, United States of America. It was a double-blind, peer-reviewed study, published in the Innovative Journal of Research in Marketing and Customer Success. The study sought to investigate the awareness and adoption of digital marketing strategies among Small and Medium Enterprises (SMEs) in Lagos State, Nigeria. This paper meets the eligibility criteria for a quantitative research critique due to its research design. The study evaluated in three (3) sections to provide a comprehensive assessment of the research. Merrigan and Huston (2014), as well as Cresswell and Cresswell (2018), are the underpinning books used for this review. Both are widely cited in the social sciences and education. They provide extensive foundations on quantitative research designs and methodological justifications. Peer-reviewed journals in the social sciences that carried out similar studies in Nigeria on SMEs' digital marketing strategies were also used to assess the paper’s quality, relevance, and originality against established benchmarks.